2021
DOI: 10.3389/fpubh.2021.628744
|View full text |Cite
|
Sign up to set email alerts
|

Availability, Affordability, Access, and Pricing of Anti-cancer Medicines in Low- and Middle-Income Countries: A Systematic Review of Literature

Abstract: Background: Cancer is the second leading cause of death globally accounting for more than half of deaths in Low- and Middle-Income Countries (LMICs). Cancer treatment is expensive and the high prices of cancer medicines have a huge impact on access in LMICs. Scarcity of pricing or affordability data is one of the major barriers in the development of effective and transparent pricing policies in LMICs. This study aimed to conduct a systematic review of the literature regarding pricing, availability, affordabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 27 publications
2
45
1
Order By: Relevance
“…The high cost of immunotherapies in anti-cancer treatment has been a long-term issue globally, also and particularly in low-and middle-income countries (27). To bring down prices and thus improved affordability of medicines, the Chinese government has overhauled its policy toolbox by promoting universal health insurance (28), expanding investment on biosimilar medicines (29), and conducting medical centralized volume procurement (30).…”
Section: Discussionmentioning
confidence: 99%
“…The high cost of immunotherapies in anti-cancer treatment has been a long-term issue globally, also and particularly in low-and middle-income countries (27). To bring down prices and thus improved affordability of medicines, the Chinese government has overhauled its policy toolbox by promoting universal health insurance (28), expanding investment on biosimilar medicines (29), and conducting medical centralized volume procurement (30).…”
Section: Discussionmentioning
confidence: 99%
“…Countries have also responded to its evolving normative value over time, with the inclusion of comparatively expensive and patented antiretroviral medicines in 2002 marking a pivotal moment in WHO EML’s history [ 1 ]. In recent years, the inclusion of high-priced medicines, such as for cancer and hepatitis C [ 16 , 53 ], have seen WHO’s Expert Committee on essential medicines using WHO EML proactively to promote greater affordability and access [ 54 ]. Attention has also focused on the functioning of WHO EML within the larger goal of health systems strengthening [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the review identified the relationship between revisions to NMLs and the use of HTAs to be underdeveloped. Since 2015, successive versions of WHO EML have seen additions of patented high-cost medicines [ 16 , 53 ]. These drugs have provoked the access to medicines debate in HICs and reinforced the idea that high-cost drugs are a challenge for all health systems, regardless of a country’s economic status [ 16 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high cost of ICIs has always been a hindrance to the use of immunotherapy worldwide, especially where health resources are lacking or are unevenly distributed ( 29 ). In the CheckMate9ER study, the combination of immunotherapy and targeted therapy resulted in sustained clinical benefits of improving the QOL of patients with RCC ( 14 ).…”
Section: Discussionmentioning
confidence: 99%